2013
DOI: 10.1172/jci69600
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine and cancer: cell biology, physiology, and clinical opportunities

Abstract: Glutamine is an abundant and versatile nutrient that participates in energy formation, redox homeostasis, macromolecular synthesis, and signaling in cancer cells. These characteristics make glutamine metabolism an appealing target for new clinical strategies to detect, monitor, and treat cancer. Here we review the metabolic functions of glutamine as a super nutrient and the surprising roles of glutamine in supporting the biological hallmarks of malignancy. We also review recent efforts in imaging and therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
950
2
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,043 publications
(976 citation statements)
references
References 81 publications
13
950
2
11
Order By: Relevance
“…In addition to glucose, activated B cells need amino acids for synthesis of antibodies and other proteins, as well as nitrogen, for nucleotide synthesis and other processes (Calder, 2006;Grohmann and Bronte, 2010). As the most abundant amino acid in serum, glutamine is a readily available nutrient for most cells, and is involved in providing nitrogen for synthesis of many amino acids (Caro-Maldonado et al, 2014;Hensley et al, 2013). Several genes associated with amino acid transport and biosynthesis are induced under starvation conditions in various cell types, including B cells (Le et al, 2012;Shotwell et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to glucose, activated B cells need amino acids for synthesis of antibodies and other proteins, as well as nitrogen, for nucleotide synthesis and other processes (Calder, 2006;Grohmann and Bronte, 2010). As the most abundant amino acid in serum, glutamine is a readily available nutrient for most cells, and is involved in providing nitrogen for synthesis of many amino acids (Caro-Maldonado et al, 2014;Hensley et al, 2013). Several genes associated with amino acid transport and biosynthesis are induced under starvation conditions in various cell types, including B cells (Le et al, 2012;Shotwell et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine utilization via glutaminase (glutaminolysis) provides cancer cells with glutamate that, becoming in turn oxaloacetate, may enter the TCA cycle and partially substitutes for glucose (glutamine anapleurosis). [10][11][12][13] In addition to dependency on glutaminolysis, the majority of human cancers, including breast, colon, ovary, lung, and prostate tumors express high levels of fatty acid synthase (FAS), a key metabolic enzyme that is functional to catalyze the synthesis of long chain saturated fatty acids for supporting the increased demand for membrane biogenesis. 14,15 The therapies currently employed to limit tumor expansion mostly utilize cocktails of antineoplastic drugs that interfere with the cell cycle progression; these agents include cell cycle specific drugs like plant alkaloids (etoposide, topotecan) or DNA synthesis inhibitors (5-fluorouracil, methotrexate) and cell cycle non-specific drugs like crosslinking agents (cyclophosphamide, ifosfamide, cisplatin) or intercalating anthracycline antibiotics (doxorubicin, daunorubicin).…”
mentioning
confidence: 99%
“…Glutamate serves as a source of amino groups for NEAA production, particularly aspartate and alanine. This set of reactions transfers amino groups between glutamate and α-ketoacid which is used to synthesize proteins [16]. Moreover, glutamate can enter into mitochondria and be oxidized to α-ketoglutarate (α-KG), reducing NADP + to NADPH or NAD + to NADH and produces a second molecule of NH 4+ .…”
Section: Glutamine Metabolismmentioning
confidence: 99%
“…Subsequent in vitro and in vivo experiments have suggested that the monitoring of glutaminolysis could be exploited to generate imaging tracer diagnostics to benefit cancer patients [162,163]. Currently, there have been a number of clinical trials in patients using different radioisotopes, like 11 C, 13 N, or 18 F to image glutamine [16]. Moreover, detailed metabolic maps have been extensively studied in many cancer cell types [164].…”
Section: Measuring Glutamine In Cancermentioning
confidence: 99%
See 1 more Smart Citation